PRAGMATIC STUDY AND AESTHETIC OF MORAL MESSAGES ON MEDIA IMAGE - Edy Tri Sulistyo (Proceeding of International Conference on Art, Language, and Culture, 2017)
This study attempts at exploring a philosophical-pedagogical value (message moral). The image is basically the expression of personal feelings which can be an attempt to convey basic and useful information for the society and the preservation of art and culture in Indonesia. Indonesia concerns the diversity and local wisdom values (just say the Javanese society which characteristically classified into its high culture ‘adiluhung’). The transmission of information realized through values, especially to the current society is perceived declining, thus the effort to maintain a prudent value system can be done in various ways. One of the ways in this study is its delivery with the image media. Images in question such as picture signs, billboards, posters, banners, murals and so on. The pictures are now presented / displayed in various strategic places so that the community, especially the younger generation can read it at any time. The hope is that people can implement it in everyday life. To pragmatically reveal the value (moral message), this research is qualitative descriptive. The data sources are in the form of writing utterances on the image / ad. Data analysis techniques employed holistic criticism and pragmatic analysis. The results showed that the utterances contained in the media images / ads produces some meanings to the readers and implement them in the real life activities.